Empirical Analysis of Aquaponics Farming Markets in Pune Region - Dr. Nilesh Kate,Prof. Naveen Pandey, Dr. Mahendra More, Ng. Putukho Pao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Demand for Organic Food Supply has grown exponentially in the recent years and Pune City in Particular has seen a High Demand for Aquaponics Products as it one of the most preferred location for Corporate destination and also the Aquaponics System is widely considered to be a Superior Agricultural Practice due to its economical, Scientific and Technological Advancement where Crops are grown Soil-less and without the use of Artificial Fertilizers. In Aquaponics, the crops and marine lives are mostly grown in a Controlled Environment where the cost of Energy, negative impact on Environment and the usage of Water can be minimized and efficiently used from the growing till the harvest period. Factors like Water Quality (PH and Acidity Level) should be regularly checked and maintain accordingly (6.8-7.2). This Research will further highlight the importance and development of the Aquaponics System for Small – Medium Farmers and also how it has Potential to satisfy and over produce for export purposes, increase the Employment opportunity in Rural Areas and also satisfying the demand for Organic Food Products in the Urban and Metro Cities like Pune.